Review: Jujustu Kaisen (2022)
Illustrated by Gege Akutami, Jujustu Kaisen is a manga that carries us through a world full of magic and sorcerers trying to protect the world from evil energies which create dangerous cursed sprits. Yuuji Itadori is the main character in this shōnen manga, where he will have the life and adventures of a hero beside his high school friends. Nonetheless, this shōnen is different than all others since it allows the reader to enjoy this captivating story with an accurate representation of the Japanese culture, a touch of superstition, magic, and introspection.